Proposal of interoperability of the different health information systems, as a strategy to improve the handling of information and decision-making - Auccahuasi, Wilver (2020)
ABSTRACT Health systems are in constant change, either due to technological progress or due to the same need produced by external agents such as COVID-19, which have caused an analysis of all the information systems dedicated to the various procedures in the health area, from clinical information management, information from health insurers, image information management, drug supply management, medical supplies and supplies management, among other systems specific to each health institution. It is in this environment where a lot of vital information for decision making is produced that in most cases is impossible to manage, because it is found on different platforms and in most cases in different institutions. The present research presents a methodology for the exchange of information between systems based on the interoperability of systems and using the XML standard, very similar to what the HL7 protocol advises, the implementation of the methodology can be synchronous or asynchronous depending on the degree. of need that is required to use and depending on the different users who require to share their information. The results show the practicality of the implementation and that these can be implemented in the shortest time possible using communication between messages following the protocol presented, which will depend on the information required, the implementation can be done by reading the message and loading the case system Contrary to being able to enter the system directly, its application will depend on the ease of being able to update the information systems that are running.